2010
DOI: 10.4103/0377-4929.64343
|View full text |Cite
|
Sign up to set email alerts
|

Acute eosinophilic appendicitis and the significance of eosinophil - Edema lesion

Abstract: Eight cases of a histological entity that we name 'acute eosinophilic appendicitis' (AEA) are described and compared with classical acute appendicitis and appendices, which turned out to be normal after emergency appendicectomy. These 8 cases formed part of a dataset of 128 emergency appendicectomies, which also included 78 cases of classical acute appendicitis and 42 cases of normal appendix. The clinical and pathological variables were compared between these three. Acute eosinophilic appendicitis is characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Our observation of an association between appendicitis and air pollution was corroborated by a study from Western Canada (Kaplan, et al, 2009). The significance of these observations is underscored by pathological studies linking appendicitis to eosinophilic degranulation (Santosh & Aravindan, 2008;Aravindan, et al, 2010). Seasonal variation of appendicitis with its peak associated with a season characterized by high ambient pollen and other phyto-allergens or sandstorm is an observation that can neither be explained by diet nor fecaliths but may have a bearing on immune modulation playing a role.…”
Section: Seasonal Variationsupporting
confidence: 69%
“…Our observation of an association between appendicitis and air pollution was corroborated by a study from Western Canada (Kaplan, et al, 2009). The significance of these observations is underscored by pathological studies linking appendicitis to eosinophilic degranulation (Santosh & Aravindan, 2008;Aravindan, et al, 2010). Seasonal variation of appendicitis with its peak associated with a season characterized by high ambient pollen and other phyto-allergens or sandstorm is an observation that can neither be explained by diet nor fecaliths but may have a bearing on immune modulation playing a role.…”
Section: Seasonal Variationsupporting
confidence: 69%
“…The false-negative case was a 19-year-old man with the final diagnosis of acute eosinophilic appendicitis confirmed by the surgical pathology specimen. Acute eosinophilic appendicitis was characterized by a grossly inflamed appendix with the infiltration of eosinophils (not neutrophils) in the muscularis propria [23]. This case presented with 3 hours of abdominal pain before the CT scan and had an Alvarado score of 7, and the CT images showed a normal air-filled appendix with no appendiceal wall thickening or adjacent fat stranding.…”
Section: Computed Tomographic Evaluationmentioning
confidence: 84%
“…Primary bacterial and viral infections [6], blunt abdominal trauma, and ischemia of the appendix [7] have been also investigated as possible causes. It has also been suggested that there is a genetic predisposition [8] or a type I hypersensitivity reaction involved in the development of acute appendicitis [9]. Furthermore, two hypotheses have been proposed in this regard: the "hygiene hypothesis" [10] and the "diet hypothesis" [11].…”
Section: Introductionmentioning
confidence: 99%